Fermentation of Lulo Juice with Lactobacillus reuteri CECT 925. Properties and Effect of High Homogenization Pressures on Resistance to In Vitro Gastrointestinal Digestion - Leidy Indira Hinestroza-Córdoba (MDPI AG, 2021)
The aim of this study was to evaluate the use of lulo juice as substrate for producing a potentially probiotic beverage with Lactobacillus reuteri CECT 925. Lulo juices at two pH levels and two levels of HPH treatment have been considered to evaluate the effect of these variables on Lactobacillus reuteri CECT 925 growth, physicochemical and antioxidant properties, and the resistance of microbial cells to gastrointestinal digestion in vitro. Regarding the growth of Lactobacillus reuteri CECT 925, it was mainly affected by the pH of the medium, the rectified juice at pH 5.5 being the most appropriated one. The growth of Lactobacillus reuteri CECT 925 mainly increased the antiradical capacity of the juices. In general, Lactobacillus reuteri CECT 925 showed good resistance to in vitro gastrointestinal digestion conditions, reaching levels above 107 CFU/mL in all cases. The highest resistance was observed in the juice treated at 150 MPa followed by the juice homogenized at 100 MPa.